Privatising Socially Owned Enterprises, The Case of Kosovo - Loku, Afrim; Loku, Nadire Shehu (Asian Economic and Financial Review, 2016)
This paper aims at analyzing activities, and some of the causes of economic expansion of Kosovo’s economy, mainly focused in stage of initial establishment of the private sector in Kosovo. The purpose of the paper is to present the current situation of privatization and results of this process, namely to review some of the obstacles, with a view of eliminating such obstacles and fostering development. The paper shall provide a comparison between the process and current point of privatization, with a special focus on obstacles to Kosovo’s economy. This paper shall prove an overview on the situation of privatization processes sectors, and it is an effort to mirror the main obstacles preventing from corruption and other factors. The main goal of the paper is to provide a basis for informing various actors involved in privatization process and economic development policy making in Kosovo. On the other hand, it is also an effort to contribute in consolidating information and statistical records, with a view of providing an accurate overview on Kosovo’s industry.